Strategy For Internalization of Karimah Values In Learning Islam In Al-Halim Garut Vocational School - Wiwik Dyah Aryani; Marwan Setiawan; Aceng Enin (PT. Publikasiku Academic Solution, 2022)
Background: In this modern era, how important it is to maintain harmony, harmonize development and progress, and must preserve and instill in all humans, especially students, so that education is designed as well as possible so that all students can understand and live the best. It is important to implement the moral values ??that are taught.Aim: The purpose of this study is to describe the religious development of students who seek the development of religious culture at SMP Negeri 10 Bandung.Method: This research is a type of qualitative research. The research approach used is a phenomenological approach (the meaning of existence) which is an approach to gaining knowledge about something (object) as it appears and becomes our conscious experience.Findings: shows that the implementation of student religious development through the development of religious culture at SMP Negeri 10 Bandung has been going well and programmed, both carried out by the school as a complete educational institution with wisdom related to the development of religious culture in schools and community activities carried out by Rohit ( Spiritual Islam) as a kind of extracurricular activities for special schools in the shade. other religious activities. This success can be achieved because of the efforts of the principal and the support of the entire school community by showing commitment that each goes together and supports the other